On the presence of aluminium in human endometrial tissue and potential factors that may influence it – a pilot study (Journal of Medical Science, 2014)
Introduction. Aluminium (Al), the most ubiquitous metal in the earth crust, has been shown to reveal a potential metalloestrogenic action. Despite an increasing interest in Al exposure in human, there is essentially no information on its status in the reproduction system. Aim. The present work investigated the content of Al in female endometrial tissue (n = 25) and its association with endometrial thickness and histological image, female age, place of living, history of cigarette smoking and diet. Material and methods. The endometrial samples (n = 25) were obtained during routine procedures. The Al content was determined using microwave induced nitrogen plasma atomic emission spectrometer. The relationships between metal level and histological image, endometrial thickness, female age, place of living, cigarette smoking and diet were investigated. Results. The Al was detected in every analysed sample. Its concentrations varied from 0.9–16.0 µg/kg dry tissue. The lowest Al level was found in atrophic endometrium. The metal content in polyposis, hyperplasia and unaltered tissue was comparable. The study failed to find significant association with the metal content and endometrial thickness, female age, place of living, smoking habits and diet. Conclusion. Human endometrial tissue can contain detectable levels of Al. It, in turn, indicates that endometrium may play a role in systematic accumulation of absorbed Al but also that it may represent an unique route of periodic discharge of this element. Further studies are necessary to elucidate which factors are responsible for the presence of Al in endometrium and what are the possible consequences of its increased content in this tissue.